Aplikasi Perkembangan Stadia Hidup Nematoda Puru Akar (Meloidogyne spp.) Mulai Dari Fase Telur Sampai Dewasa pada Pertanaman Tomat (Solanum lycopersicum L.) di Kota Banjarbaru - Raihana Raihana; Dewi Fitriyanti; Zairin Zairin (Universitas Lambung Mangkurat, 2018)
Meloidogyne spp. is the cause of dwarf symptoms, yellowing, wilting and the formation of bumps on the roots of tomatoes which leads to decreased production of quality and quantity of tomatoes. Observation of nematode life cycle is important to design an effective and efficient control strategy, by knowing the life cycle of Meloidogyne spp. can be known how to control and when the right application time to control the parasite Meloidogyne spp. Inoculation of nematode eggs is done by pouring a suspension containing 300 nematode eggs around tomato roots. Observation of the life cycle of nematodes in the roots was done by the method of tissue staining Byrd et al, (1983). Temperature was measured to determine its effect on the length or length of development of live stages of Meloidogyne spp. the. Long development of live stadia Meloidogyne spp. starting from the egg phase, L2, L3 + L4 and adult male / female.on tomato plants in Banjarbaru is 14 days with temperature range 22.6 ⁰C - 33.6 ⁰C.